Period of Introduction and Role of Archigalli in Context of the Inscription of L. Publicius Syntropus from Koper (Archaeologia Adriatica, 2012)
In the paper author discusses and interprets funerary inscription of the archigallus Lucius Publicius Syntropus from Koper dated in the period between the end of the 1st century and the 3rd century AD. The author also discusses the period of introduction of archigallus and its role in the cult of Magna Mater and Atis. Metroac cult and Metroac community in the coastal part of Regio X is also analysed with the aim of positioning archigallus L. Publicius Syntropus in historical and geographical context.
Keywords: archigalli; galli; Magna Mater; Attis; cult; Koper